2014
DOI: 10.4209/aaqr.2013.09.0287
|View full text |Cite
|
Sign up to set email alerts
|

Diwali Fireworks: Early Signs of Impact on PM10 Properties of Rural Brahmaputra Valley

Abstract: The festival of Diwali and it associated fireworks, which were not so common in the past, are slowly penetrating into rural Brahmaputra Valley. PM 10 monitoring was done during the 2009 Diwali festivities at a rural site in the Brahamputra Valley of Northeast India. Sampling of PM 10 was done on a 12 hourly basis for an extended period of 13 consecutive days. The mean PM 10 concentration during the monitoring campaign was found to be 40.88 ± 19 µg/m 3 and the maximum concentration of PM 10 was recorded on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Table 2 presents a comparison of PM 10 and metals concentrations during Diwali in the present study with other studies around the world 17,18,20,39,43,44,45. The metal concentrations in the present study, except for Fe and Zn, were higher than in other studies.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…Table 2 presents a comparison of PM 10 and metals concentrations during Diwali in the present study with other studies around the world 17,18,20,39,43,44,45. The metal concentrations in the present study, except for Fe and Zn, were higher than in other studies.…”
Section: Resultssupporting
confidence: 50%
“…A previous study in northeast India observed an increase in the concentrations of metals, anions and cations during festival days compared to other days 18. In Raipur, ion concentrations were 10 times greater than other days 19.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Khaparde, Pipalatkar, Pustode, Rao, and Gajghate (2012) in Nagpur (Central India) reported a 4-10fold increase in PM 10 concentration was observed during Diwali. A previous study in northeast India observed an increase in the concentrations of metals, anions, and cations during festival days compared to other days (Deka & Hoque, 2014). Garaga and Kota (2018) indicated that the mean PM 10 concentration during Diwali, 311 µg/m 3 , was 81% higher than other days and 3.1-times higher the Indian National Ambient Air Quality Standards.…”
Section: Introductionmentioning
confidence: 76%